DAKWAH TOLERANSI DI INDONESIA:: Kontekstualisasi Hadis Penghancuran Masjid Pada Masa Nabi Muhammad SAW - MUHMAD IRHAMDI; YUSRI HAMZANI (UIN Mataram, 2021)
The house of worship is one of the sacred places in a religious community. In addition, the house of worship is also one of the important icons in a religion. In the context of Islam, the Prophet Muhammad once ordered to destroy houses of worship. This is certainly contradictory to the house of worship as a sacred and iconic place. This paper discusses further about the traditions of the destruction of the house of worship. In addition, this paper also contextualizes the universal values ??of the hadith with the context of religion in Indonesia. The double movement theory initiated by Fazlur Rahman which was further developed by Abdullah Saeed becomes a point of view in analyzing this reality. If we go back to past history, the order to destroy houses of worship at the time of the Prophet was caused by the existence of mosques that did not benefit the Muslim community. On the contrary, the mosque was used to spy on the Muslim community at that time. If you look at the context, then the destruction of mosques in Indonesia by using the hadith as a justification is certainly not appropriate because the context is different.